2023
DOI: 10.31067/acusaglik.1240702
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Beliefs and Barriers of Healthcare Workers about Human Papilloma Virus (HPV) and HPV Vaccination

Abstract: Background/Purpose: HPV vaccine is critical in the primary prevention of HPV infection and related diseases. HPV vaccination alone reduces HPV infection by 70% and cervical cancer by 48%. Healthcare workers are expected to have sufficient knowledge and positive attitudes and behaviours about the HPV vaccine. This study aimed to determine the knowledge level of healthcare workers about HPV and HPV vaccination and their beliefs and barriers towards HPV vaccination. Methods: In this cross-sectional study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…16 In recent studies with HCWs, most of whom were physicians, the rates of those who had heard of the HPV vaccine were 87.2% and 94.4%, respectively. 17,18 The reason why these rates were found to be higher may be the high number of physicians in these studies. In fact, as in the current study, it has been reported that the level of HPV knowledge of physicians is higher than that of other HCWs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…16 In recent studies with HCWs, most of whom were physicians, the rates of those who had heard of the HPV vaccine were 87.2% and 94.4%, respectively. 17,18 The reason why these rates were found to be higher may be the high number of physicians in these studies. In fact, as in the current study, it has been reported that the level of HPV knowledge of physicians is higher than that of other HCWs.…”
Section: Discussionmentioning
confidence: 85%
“…19 Similar to our study, some studies reported that the most frequently referenced source of information about HPV vaccines was professional resources (courses/congresses, scientific literature, expert physician opinions, etc.). 17,19 It has also been determined that the knowledge level of HPV and HPV vaccines is higher among those who use professional sources as information sources. 19 Although we did not find any statistical significance, this was also true in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation